Macroeconomic Spillover and Single Currency Adoption: An Inter-regional Analysis - Agyapong, Daniel (SPOUDAI Journal of Economics and Business, 2014)
The merging and sustenance of the economies of different countries require the integration of several aspects of those economies, including price levels and money market activities. The member countries within the West African Monetary Zone have resolved to introduce a single currency, the ECO. It is therefore, necessary to assess their readiness by testing how key macroeconomic indicators from these countries relate. Using the recent innovative accounting methodology to test if there are differences in the way these countries respond to shocks from the major markets after a decade of setting convergence criteria to harmonize their economies. The paper used a monthly money market indicator (interest rate) and price levels (consumer price indices) for the period between January, 1990 and December, 2010. The results indicate that the countries’ respond differently to shocks from the major markets (i.e. China, United States and United Kingdom). This is an indication that the countries are yet to be integrated to pave the way for the introduction of the common currency. JEL Classification: F31; F36; GI5.